Preparation of Space Experiments 2020
DOI: 10.5772/intechopen.93464
|View full text |Cite
|
Sign up to set email alerts
|

Aircraft Parabolic Flights: A Gateway to Orbital Microgravity and Extra-Terrestrial Planetary Gravities

Abstract: Aircraft parabolic flights provide repetitively periods of reduced gravity whose duration depends on the target reduced gravity level and on the type of aircraft used. Typical durations for a large aircraft vary between approximately 20 s for a 0 g environment and 32 s for a Martian g level environment. Parabolic flights are used to perform short duration scientific investigations in weightlessness or at partial-g levels, to train astronauts, and to allow the general public to experience what astronauts' encou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Based on the altitude of the aircraft over time, as shown in figure 4, the equation of motion y(t) during the parabola phase is a quadratic function. To achieve a true state of free fall, the pilots must neutralise all the forces acting on the aircraft (aerodynamic lift, aerodynamic drag and engine thrust) in addition to the force of gravity [1]. Under the aforementioned conditions and considering that the aircraft's trajectory is flat, in a first approximation, the law of motion for the vertical position of the aircraft can be written like…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the altitude of the aircraft over time, as shown in figure 4, the equation of motion y(t) during the parabola phase is a quadratic function. To achieve a true state of free fall, the pilots must neutralise all the forces acting on the aircraft (aerodynamic lift, aerodynamic drag and engine thrust) in addition to the force of gravity [1]. Under the aforementioned conditions and considering that the aircraft's trajectory is flat, in a first approximation, the law of motion for the vertical position of the aircraft can be written like…”
Section: Resultsmentioning
confidence: 99%
“…0 From the equations of the fit curves to the altitude data, in figure 8, as well as from the equations (3)-( 4), we can obtain the values of the acceleration of aircraft relative to the Earth, a . Taking into account that the Earth's acceleration of gravity at altitude of 8 km is = g −9.78 m s −2 [20], the acceleration of gravity felt inside the aircraft, ¢  g , can be determined by equation (1). Therefore, for the Martian parabola, ¢ g is −3.96 m s −2 and for the lunar parabolas ¢ g is −1.87 m s −2 and −1.85 m s −2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cellular, animal, and human studies performed in simulated or real microgravity demonstrated influences of weightlessness and gravity on haemostasis and, in particular, on platelets, even if available data depict a contrasting picture probably due to the differences in unloading conditions. Briefly, it should be recalled that experiments in real microgravity can be performed only in orbit, i.e., onboard space stations or rockets and capsules, while short duration of reduced gravity can be achieved by parabolic flights ( Pletser, 2020 ). Ground-based analogues for human spaceflight, such as immersion and head down tilt bed rest, are available, but present some limits ( Pandiarajan and Hargens, 2020 ).…”
Section: Platelets In Spacementioning
confidence: 99%